(untitled) (IUBAT Review, 2025)
Metallomesogenic compounds are an emerging class of materials combining optical, magnetic, and electrical properties, offering great promise for applications in display devices, sensors, and molecular electronics. In this study, a novel copper(II)-based metallomesogen, [Cu(Cm)(S)₂](J)₂·2H₂O, was synthesized through a four-step synthetic strategy involving cyclam (Cm = 1,4,8,11-tetraazacyclotetradecane), 4-hexadecy-loxypyridine (S), and 4-chlorobenzoate ions (J). Comprehensive characterization was performed using elemental analysis, FTIR, UV-Vis spectroscopy, magnetic susceptibility measurements, TGA, DSC, and polarized optical microscopy (POM). Elemental examination proved the proposed formula, and UV-Vis spectroscopy indicated a trans-III octahedral geometry around the Cu(II) center. The complex exhibited a magnetic moment (µeff) of 1.7 B.M., typical for mononuclear copper(II) complexes. TGA demonstrated multistep thermal decomposition, while DSC revealed three broad endothermic transitions associated with crystal-to-mesophase, mesophase-to-isotropic, and subsequent cooling transitions. POM analysis further confirmed the formation of mesophases, highlighting the compound’s mesogenic behavior. The successful synthesis and detailed study of [Cu(Cm)(S)₂](J)₂·2H₂O provide important insights into the design of new metallomesogens with tunable physical properties, expanding opportunities for future development in advanced materials for electronic and optoelectronic applications. IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 65-84